A 3D Organically Synthesized Porous Carbon Material for Lithium‐Ion Batteries. Issue 37 (4th July 2018) - Zhao, Ziqiang; Das, Saikat; Xing, Guolong; Fayon, Pierre; Heasman, Patrick; Jay, Michael; Bailey, Steven; Lambert, Colin; Yamada, Hiroki; Wakihara, Toru; Trewin, Abbie; Ben, Teng; et al.
Abstract: We report the first organically synthesized sp–sp 3 hybridized porous carbon, OSPC‐1. This new carbon shows electron conductivity, high porosity, the highest uptake of lithium ions of any carbon material to‐date, and the ability to inhibit dangerous lithium dendrite formation. The new carbon exhibits exceptional potential as anode material for lithium‐ion batteries (LIBs) with high capacity, excellent rate capability, long cycle life, and potential for improved safety performance. Abstract : What you C is what you get : The first 3D sp–sp 3 hybridized porous carbon material to be prepared by organic synthesis has a high conductivity. The new carbon exhibits exceptional potential as anode material for lithium‐ion batteries (LIBs) with high capacity, excellent rate capability, long cycle life and potential for improved safety performance.